(untitled) (MAUSAM, 1956)
It is found that summer months at Ahmedabad are marked by the arrival, of sea breeze from, the Gulf of Cambay (abbut50 miles to the south) during the evening hours. The occurrence of sea-breeze is more frequent and its effect more pronounced in the months of May and June. A few statistical data relating to this sea breeze are given in this paper.